The Symbolic Meanings of the European Union Flag : The Case of Croatia - Trako Poljak, Tijana (2012)
Herbert Blumer (1969) argued that people act toward objects on the basis of meanings, which emerge not only from the things themselves but from the interpretative process. This paper uses the example of the European Union flag in order to examine the construction of meanings through social interaction. It relies on semiotics and constructivism approach in order to show that the construction of meaning of a symbol such as the EU flag occurs at all levels of the communication process: senders of the message (political elites), receivers and their interpretations (member-states), as well as the symbol itself. Firstly, the meanings ascribed to the EU flag by the EU officials will be examined to show that there is not always a unified narrative among the senders of the message. Secondly, the origins of the design of the flag will be looked at to show that the multivocality arises from the meanings of the object itself. Finally, the introduction of the symbol in EU member-states creates further complicacy. Croatia, which is on the eve of the EU accession, where the EU flags have been waved in public spaces since 2004, will be used as an example to show what additional meanings are ascribed to this political symbol stemming from specific historic and socio-cultural context of the receivers. In the end, a brief overview of 2010 empirical research using the semantic differential method on the representative sample of Croatian population will be given which looked further at how individual socio-demographic characteristics influence the attitudes of the recipients towards the EU flag.